Complete mitochondrial genome of Favonigobius gymnauchen (BLEEKER, 1850) assembled from next-generation sequencing data. Issue 2 (3rd July 2019) - Jo, Hyunbin; Park, Kiyun; Kim, Dong-Kyun; Kwak, Ihn-Sil
Abstract: The complete mitochondrial genome of Favonigobius gymnauchen was sequenced. The circular mitochondrial genome is 16, 480 bp and consists of 13 protein-coding, 2 ribosomal RNAs, and 13 transfer RNA genes (GenBank accession no. MN194589). Results of maximum likelihood analysis showed that this species clustered with other species of the family Gobbidae. This study will contribute to the phylogenetics of genus Favonigobius and the other genera of Gobiidae.